Impact of Population Stratification on Family-Based Association in an Admixed Population - T. B. Mersha; L. Ding; H. He; E. S. Alexander; X. Zhang; B. G. Kurowski; V. Pilipenko; L. Kottyan; L. J. Martin; D. W. Fardo (International Journal of Genomics)
Population substructure is a well-known confounder in population-based case-control genetic studies, but its impact in family-based studies is unclear. We performed population substructure analysis using extended families of admixed population to evaluate power and Type I error in an association study framework. Our analysis shows that power was improved by 1.5% after principal components adjustment. Type I error was also reduced by 2.2% after adjusting for family substratification. The presence of population substructure was underscored by discriminant analysis, in which over 92% of individuals were correctly assigned to their actual family using only 100 principal components. This study demonstrates the importance of adjusting for population substructure in family-based studies of admixed populations.